Sustainable management models: innovating through Permaculture. Issue 1 (13th February 2017) - Vitari, Claudio; David, Christophe
Abstract : Purpose: Exploring the ways in which innovation can serve to create better and more integrated social, environmental, and economic enterprises is a key challenge. How firms innovate and change depends strongly on their management models. Permaculture concepts and principles could help the transition toward more sustainability. The purpose of this paper is to understand how management models could rely on Permaculture principles to facilitate innovations and changes toward sustainability. Design/methodology/approach: This paper helps meet this challenge by exploring possible innovative management models that could help in pursuing sustainability by aligning enterprises with socio-ecological realities. The possible innovative management models built on the Permaculture concepts will be the object of analysis for this study. Findings: The literature review shows that there could be innovative management models built on the Permaculture concepts, a potential alternative to western "traditional" management models. They would give preference to long-term objectives, intrinsic motivation, emergent coordination, and collective wisdom in decision making. Originality/value: It is strategically important to find new concepts, models, methods, and practices that will lead society to be ecologically sustainable and socially responsible, besides being economically efficient. These socio-cultural and economic challenges are central to the design and construction of a society in which all individuals feel integrated and responsible.